Hubungan Perkembangan Kognitif Peserta Didik Dengan Proses Belajar - Artawijaya, Anak Agung Ngurah Bayu; Saptiari, Ni Made (Metta : Jurnal Ilmu Multidisiplin, 2023)
Cognitive development in students has recently been in the spotlight among educational institutions. This cognitive or knowledge development is able to influence the level of quality of human resources which can have an impact on the progress of a country. If we talk about students' cognitive development, it is certainly part of the psychology of learning. The aim of this research is to determine the cognitive relationship between students and the learning process. This research uses qualitative research with literature study. The data analysis technique in this research was carried out descriptively based on research results obtained through observation, interviews and documentation. The results of this research show that cognitive development and the learning process are related to each other. The learning process can be said to be successful if students are able to understand and absorb knowledge which can then be applied by students. Cognitive development is very important in the student's learning process, taking into account the successful development of the cognitive domain can have a positive impact on the affective and psychomotor development process. Therefore, it is critical for educators to work on students' cognitive abilities as well as develop foundational skills for active learning, which ultimately promotes development in other psychological domains in students.